Winfield Scott Schley papers - Schley, Winfield Scott, 1839-1911.
Chiefly personal letters written by Schley or his wife, Anne R. Franklin Schley, to Florence W. Schley and Frederick Schley. Also includes an obituary for Frederick Schley.
Naval officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Schley, Anne R. Franklin -- Correspondence; Schley, Florence W. -- Correspondence; Schley, Frederick, -- 1814-1875 -- Correspondence; Schley family; United States. -- Navy -- Officers; Naval officers